High Dietary Sodium, Measured Using Spot Urine Samples, is Associated with Higher Blood Pressure among Young Adults in Haiti. Issue 1 (14th February 2023) - Clermont, Adrienne; Rouzier, Vanessa; Pierre, Jean Lookens; Sufra, Rodney; Dade, Eliezer; Preval, Fabyola; St-Preux, Stephano; Deschamps, Marie Marcelle; Apollon, Alexandra; Dupnik, Kathryn; Metz, Miranda; Duffus, Yanique; et al.
Background: Hypertension (HTN) is the leading cardiovascular disease (CVD) risk factor in Haiti and is likely driven by poverty-related social and dietary factors. Salt consumption in Haiti is hypothesized to be high but has never been rigorously quantified. Methods: We used spot urine samples from a subset of participants in the population-based Haiti Cardiovascular Disease Cohort to estimate population mean daily sodium intake. We compared three previously validated formulas for estimating dietary sodium intake using urine sodium, urine creatinine, age, sex, height, and weight. We explored the association between dietary sodium intake and blood pressure, stratified by age group. Results: A total of 1, 240 participants had spot urine samples. Median age was 38 years (range 18–93), and 48% were female. The mean dietary sodium intake was 3.5–5.0 g/day across the three estimation methods, with 94.2%–97.9% of participants consuming above the World Health Organization (WHO) recommended maximum of 2 g/day of sodium. Among young adults aged 18–29, increasing salt intake from the lowest quartile of consumption (<3.73 g/day) to the highest quartile (>5.88 g/day) was associated with a mean 8.71 mmHg higher systolic blood pressure (SBP) (95% confidence interval: 3.35, 14.07; p = 0.001). An association was not seen in older age groups. Among participants under age 40, those with SBP ≥120 mmHg consumed 0.5 g/day more sodium than those with SBP <120 mmHg (95% confidence interval: 0.08, 0.69; p = 0.012). Conclusions: Nine out of 10 Haitian adults in our study population consumed more than the WHO recommended maximum for daily sodium intake. In young adults, higher sodium consumption was associated with higher SBP. This represents an inflection point for increased HTN risk early in the life course and points to dietary salt intake as a potential modifiable risk factor for primordial and primary CVD prevention in young adults.